Gadamers Erbe und die Zukunft der Hermeneutik - Arnold, Florian; Feige, Daniel Martin (Reality and Hermeneutics, 2025)
Gadamers philosophical hermeneutics enjoys an ongoing reception. Following the path this has historically taken and with a view to future developments, the present contributions locate Gadamers thinking at the centre of contemporary debates, both in philosophy and beyond.